Nilai Budaya dan Kinerja Environmental, Social, Governance (ESG) : A Systematic Literature Review - Rahma Rina Wijayanti; Oryza Ardhiarisca; Berlina Yudha Pratiwi; Dwi Indriani Fidiastutik Wijaya (Politeknik Ganesha Medan, 2026)
This study presents a Systematic Literature Review (SLR) examining the interplay between culture and governance in shaping Environmental, Social, and Governance (ESG) practices across corporate, community, and societal contexts. Bases on PRISMA reporting flow, total of 41 relevant articles published between 2015–2025 were synthesized to map how cultural values function as informal governance that moderates, mediates, or reinforces sustainability implementation and performance. The review identifies five primary cultural influence pathways: board and organizational culture, national traditions and collective values, innovation and digital culture, local wisdom and social capital, as well as investor perception shaped by cultural context. These mechanisms significantly impact ESG disclosure quality, long-term decision-making, stakeholder legitimacy, and environmental innovation, although the effects vary across institutional settings. The findings reveal research gaps related to fragmented scholarly approaches, inconsistent outcomes on cultural diversity, and the absence of multi-level integrated models. This study highlights culture as a foundational mechanism in sustainability governance beyond regulatory compliance and encourages future studies to develop longitudinal, mixed-method, and cross-country comparative frameworks.